Three sisters, three queens - Gregory, Philippa (London : Simon & Schuster, 2016)
United in sisterhood by birth and marriage, Katherine of Aragon, Queen of England, Margaret Tudor, Queen of Scots, and Mary Tudor, Queen of France immediately recognize each other as both allies and rivals in the treacherous world of court and national politics. Their bonds extend beyond natural and expeditious loyalties, as romance, scandal, war, and religion inextricably unite these three for better or for worse.
Includes bibliographical references.
Keywords: Henry -- VIII, -- King of England, -- 1491-1547 -- Fiction; Catherine, -- of Aragon, Queen, consort of Henry VIII, King of England, -- 1485-1536 -- Fiction; Henry, -- King of England -- VIII, -- 1491-1547 -- Fiction; Margaret, -- Queen, consort of James IV, King of Scotland, -- 1489-1541 -- Fiction; Mary, -- Queen, consort of Louis XII, King of France, -- 1496-1533 -- Fiction; Queens -- France -- Fiction; Queens -- Great Britain -- Fiction; Sisters -- England -- Fiction; Queens -- England -- Fiction; Great Britain -- History -- Tudors, 1485-1603 -- Fiction; Historical -- Print; Historical fiction; Biographical fiction; Biographical fiction; Historical fiction